2014
DOI: 10.1007/s13762-014-0532-0
|View full text |Cite
|
Sign up to set email alerts
|

Deadwood assessment in different developmental stages of beech (Fagus orientalis Lipsky) stands in Caspian forest ecosystems

Abstract: Deadwood is an indicator that addresses many parameters of naturalness and is becoming a general reference for natural forests. If there are enough of the different kinds of deadwood in a forest, then it is likely to be properly natural. Also, it is a practical indicator, representing the health and biodiversity of forests. The aim of this research was to find out how much deadwood should be present in different developmental stages in a natural forest as a reference. For this purpose, a natural forest ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
6
0
2
Order By: Relevance
“…Focusing on south-western European forests, Alberdi et al [17] found that the species composition of the stand has a strong influence on the amount of deadwood in mixed forests that showed double the volume of deadwood than that of pure conifer and broadleaf stands [17], confirming the findings of a previous study conducted in China [18]. On the other hand, little is known regarding the impact of different forest management systems on deadwood (in particular snags) volume and decay stage in Iranian forests where previous studies focused mostly on natural unmanaged forests [19,20].…”
Section: Introductionsupporting
confidence: 77%
“…Focusing on south-western European forests, Alberdi et al [17] found that the species composition of the stand has a strong influence on the amount of deadwood in mixed forests that showed double the volume of deadwood than that of pure conifer and broadleaf stands [17], confirming the findings of a previous study conducted in China [18]. On the other hand, little is known regarding the impact of different forest management systems on deadwood (in particular snags) volume and decay stage in Iranian forests where previous studies focused mostly on natural unmanaged forests [19,20].…”
Section: Introductionsupporting
confidence: 77%
“…Larrieu et al (2014) reported that deadwood availability remained more or less stable throughout the silvigenetic cycle, both in terms of quantity and diversity, and whether the forests were dominated by broadleaves or conifers. However, numerous studies from different geographic regions of the world showed large variation in the amount of deadwood depending on forest type and stage of forest development (Burrascano et al 2008;Lombardi et al 2008Lombardi et al , 2012Karjalainen and Kuuluvainen 2002;Mataji et al 2014). For example, in natural spruce-beech forest stands in the Krkonoše National Park, Czech Republic deadwood measurements revealed from 27.7 to 241.6 m 3 /ha depending on the site and year of survey.…”
Section: Deadwood Volume and Forest Typementioning
confidence: 99%
“…Dead wood has been recognized as an important component of natural forests since it enriches forest ecosystems in terms of plant, fungus, and animal diversity [1][2][3][4][5][6]. It provides micro-habitats for several species and nutrients through the contribution of organic matter.…”
Section: Role and Mapping Of Dead Woodmentioning
confidence: 99%